Congenital Heart Disease in Pediatric and Adult Patients Anesthetic and Perioperative Management - Dabbagh, Ali.; Conte, Antonio Hernandez; Lubin, Lorraine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Congenital Heart Disease in Pediatric and Adult Patients: Anesthetic and Perioperative Management provides a comprehensive, up-to-date overview of care of the pediatric patient undergoing cardiac surgery and anesthesia. After introductory chapters that encompass pediatric cardiovascular embryology, physiology and pharmacology, diagnostic approaches and preoperative considerations are explained. The intraoperative management of a wide range of specific lesions is then discussed, with full descriptions of anesthesia plans added with descriptions on diagnostic methods and surgical interventions. Postoperative care is also addressed, and a concluding section considers anesthesia outside the cardiac operating room. In the twenty-first century, advances in minimally invasive technology have led to the introduction of a wide array of pediatric cardiac procedures. More traditional surgical procedures have also been transformed by new devices and surgical approaches. The cardiac anesthesiologist is faced with an ever-increasing role in the perioperative care of pediatric patients undergoing cardiologic procedures in operating rooms, as well as less conventional locations. In this book, accomplished experts from around the world in the fields of pediatric anesthesia, cardiology, and cardiac surgery describe the multiple facets of caring for this very unique patient population.
History of Pediatric Anesthesia & Pediatric Cardiac-Congenital Surgery -- Cardiovascular system embryology and development -- Pediatric Cardiovascular Physiology -- Cardiovascular Pharmacology in Pediatric Patients with Congenital Heart Disease -- Perioperative Care of the Congenital Cardiac Patient in the Cardiac Catheterization Laboratory -- Perioperative Imaging for the Congenital Cardiac Patient -- Pediatric Cardiovascular Monitoring -- Electrocardiography: Basic knowledge with focus on fetal and pediatric ECG -- Neurologic monitoring -- Coagulation monitoring -- Respiratory monitoring -- Preoperative evaluation -- Anesthetic Management of Adults with Congenital Heart Disease -- Medical Facility Infrastructure Considerations -- Limiting the Lifetime Surgical Impact of Congenital Heart Disease and Guiding Care for the Congenital Heart Patient -- Cardiopulmonary bypass in children and infants -- Atrioventricular Septal Defect (AVSD) -- Atrial Septal Defect, Ventricular Septal Defect -- Tetralogy of Fallot -- Transposition of great vessels -- Right sided obstructive lesions -- Congenital Mitral Valve Anomalies -- Congenital anomalies of the aortic valve -- Anomalies of the aortic arch, aortic coarctation, interrupted aortic arch and vascular rings -- Patent Ductus Arteriosus -- Hypoplastic Left Heart Syndrome: Treatment Options -- Double Outlet Right Ventricle -- Double Outlet Left Ventricle (DOLV) -- Pulmonary hypertension -- RV failure, Pulmonary HTN -- Coronary artery anomalies -- Heart Transplantation and Mechanical Circulatory Support in the Congenital Heart Patients -- Postoperative Cardiovascular & Hemodynamic Management in Pediatric Cardiac Surgery -- Postoperative arrhythmias and their management -- Postoperative Respiratory Management in Pediatric Cardiac Surgical Patients -- Postoperative bleeding and coagulation management -- Postoperative Central Nervous System Management in Patients with Congenital Heart Disease -- Postoperative endocrine management -- Perioperative Pain Management in Patients with Congenital Heart Disease -- Postoperative renal management, Fluid/Electrolyte management and Acid-base disorders -- Congenital Cardiac Intensive care and Management of Cardiac arrest -- Pediatric Cardiac Surgery in Emerging Countries.
Keywords: Medicine; Anesthesiology; Cardiology; Cardiac surgery; Pediatric surgery; Medicine & Public Health; Cardiology; Cardiac surgery; Anesthesiology; Pediatric surgery